Peningkatan Pengetahuan Ibu-Ibu Peserta Posyandu di Posyandu Salak, Celengan, Tasikmadu Mengenai Pengaruh Pasteurisasi Terhadap Jumlah Koloni Bakteri pada Susu Segar dan UHT - Liss Dyah Dewi Arini; Fredericus Pramonodjati; Saryadi, Saryadi (Jurnal Pengabdian Bidang Kesehatan, 2025)
Mother is a leader in a family whose duties include managing the family's healthy food and drink needs. One of the nutritious drinks that must be consumed by family members is milk. However, many family members do not understand about pasteurization or heating and non-pasteurization in cow's milk. In milk that has undergone pasteurization, the number of bacteria is less than in milk that has not undergone pasteurization. This community service activity aims to provide an understanding to the mothers of the Posyandu in Celengan, Kaling, Tasikmadu, Karanganyar villages to find out about contamination in pasteurized and non-pasteurized milk, to provide counseling to the mothers of the Posyandu about pasteurized milk and non-pasteurized milk. The counseling method is carried out using the lecture method and explanations about pasteurized and non-pasteurized milk and bacterial contamination in milk with posters and power points. The results of this community service activity are that the mothers of the Posyandu understand the differences between pasteurized and non-pasteurized milk and the presence of more bacterial contamination in non-pasteurized milk. The conclusion of this community service activity is that Posyandu mothers can learn the benefits of pasteurized milk for the body.